2020
DOI: 10.1103/physrevresearch.2.033294
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of charge transfer in thermally-expanded and strain-stabilized TIPS-pentacene thin films

Abstract: We present an extensive study of the optical and electronic properties of TIPS-pentacene thin films utilizing in situ x-ray diffraction, polarized optical spectroscopy, and ab initio density functional theory. The influence of molecular packing on the properties are reported for thin films deposited in the temperature range from 25 • C to 140 • C and for films that are strain stabilized at their as-deposited lattice spacings after cooling to room temperature. Anisotropic thermal expansion causes relative displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…In contrast, spectra of the more concentrated TIPS-Pn:PMMA blend F 1 ( B ) featured an ∼0.14 eV (∼50 nm) red-shift of the 0–0 energy (1.78 eV) and significant peak broadeningfeatures similar to those in pristine polycrystalline TIPS-Pn films F ( P ) (Figure , Figures S7 and S8). These spectral changes are due to intermolecular interactions, and they are consistent with previous studies of TIPS-Pn films and single crystals. ,,,, For example, the 0–0 red-shifts of 45–70 nm in polycrystalline TIPS-Pn films have been previously observed depending on morphology, and the large 0–0 solution–crystal red-shifts in TIPS-Pn crystals were attributed to efficient mixing of the Frenkel and charge transfer (CT) states . Furthermore, GW/BSE calculations confirmed that the lowest-energy exciton in crystalline TIPS-Pn possesses a charge transfer (CT) character and is delocalized over ∼3 nm in the a–b plane of the crystal .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, spectra of the more concentrated TIPS-Pn:PMMA blend F 1 ( B ) featured an ∼0.14 eV (∼50 nm) red-shift of the 0–0 energy (1.78 eV) and significant peak broadeningfeatures similar to those in pristine polycrystalline TIPS-Pn films F ( P ) (Figure , Figures S7 and S8). These spectral changes are due to intermolecular interactions, and they are consistent with previous studies of TIPS-Pn films and single crystals. ,,,, For example, the 0–0 red-shifts of 45–70 nm in polycrystalline TIPS-Pn films have been previously observed depending on morphology, and the large 0–0 solution–crystal red-shifts in TIPS-Pn crystals were attributed to efficient mixing of the Frenkel and charge transfer (CT) states . Furthermore, GW/BSE calculations confirmed that the lowest-energy exciton in crystalline TIPS-Pn possesses a charge transfer (CT) character and is delocalized over ∼3 nm in the a–b plane of the crystal .…”
Section: Resultssupporting
confidence: 88%
“…However, the 0– m peak ratios and the peak widths were different from those in dilute blends (Table ), which suggests that intermolecular interactions are not negligible in these films even though the lowest-energy exciton does not show spectral signatures of Frenkel–CT mixing and delocalization in these amorphous films A ( P ) . We note that, in contrast to dilute blends and amorphous films, the 0– m transitions in crystalline films are not a simple vibronic progression due to a complicated mixture of various states of Frenkel and CT nature contributing to each peak. ,, Nevertheless, in the following discussions of the crystalline films (e.g., F 1 ( B ) and F ( P ) ), the notation “0– m ” is used to differentiate between different peaks contributing to the absorption spectra in the 1.8–2.4 eV energy region for easier comparison to other films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…increase device performances, [6] as already demonstrated in the past for inorganic semiconductors, [7,8] where increase of hole and electron mobility (μ) higher than 100% have been reported for silicon transistors under strain. Finally, comparing relative trends in charge mobility as a function of the applied mechanical deformation represents a unique opportunity to validate the models describing charge transport in organic materials, since systematic errors of theories and experiments on the absolute value of the mobility become unimportant.…”
Section: Doi: 101002/adma202008049mentioning
confidence: 74%
“…Indeed, many advanced applications require either materials with a controlled yet marked electro‐mechanical response (e.g., pressure sensors [ 1,2 ] and e‐skin, a bionic device that can mimic the skin of human beings [ 3 ] ) or, conversely, materials preserving their electrical performances under mechanical deformation, for example, in flexible displays or in bioelectronic applications, [ 2,4 ] such as bio‐integrated circuits. [ 4,5 ] Moreover, inducing strain is a potential mechanism to increase device performances, [ 6 ] as already demonstrated in the past for inorganic semiconductors, [ 7,8 ] where increase of hole and electron mobility (μ) higher than 100% have been reported for silicon transistors under strain. Finally, comparing relative trends in charge mobility as a function of the applied mechanical deformation represents a unique opportunity to validate the models describing charge transport in organic materials, since systematic errors of theories and experiments on the absolute value of the mobility become unimportant.…”
Section: Introductionmentioning
confidence: 99%